Effect of water restriction and rehydration on body weight, feed and nutrient intake in indigenous hoggets (Indian Journal of Animal Production and Management, 2024)
The present experiment was conducted with objective to study effect of water restriction (WR) and  rehydration on body weight, feed and nutrient intake in indigenous hoggets under intensive production  system during summer season. Eighteen farm born unshorn Patanwadi and Marwari breeds of hoggets  were selected and randomly divided in three treatment groups on the basis of body weight (25 - 30 kg)  comprising of six in each group, viz., T1: Control (ad.lib.water), T2: (WR1-20% water restriction), T3: (WR2- 40% water restriction) for 28 days of water restriction and 4 days of rehydration. The body weight (kg), dry  matter (g/d, % and g/kg W0.75), digestible crude protein (g/d, % and g/kg W0.75) and total digestible nutrient  (g/d, % and g/kg W0.75) intake of experimental animals were comparable among treatment groups. The  body weight, dry matter and nutrient intake of experimental animals recovered significantly after 2nd day  of rehydration. The results indicated that the Patanwadi and Marwari hoggets can withstand up to 40%  water restriction during summer season under intensive production system
Keywords: Body weight; Feed and nutrient intake; Water restriction